Protection of Property - Loghinescu, Petru (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
The purpose of this paper contains establishing the genesis and evolution of the content of the peaceful enjoyment of the natural and legal person’s possessions within the European Convention on Human Rights (ECHR) system. To achieve this goal, the paper proposes objectives such as defining “possessions” under the ECHR, determining the right to property content, exploring future extensions of Article 1 of Protocol No. 1 in light of the evolution of medical sciences, and examining the relevant jurisprudence, including cases from Central and Eastern Europe. As a case study, the cases vs. the Republic of Moldova were analysed. To determine the content and development of the property protection institution within the framework of the European Convention on Human Rights, we have utilised relevant scientific research methods in the field of legal sciences as a methodological support. Logical analysis was applied throughout the study to identify the legal content of the right, which is the subject of this scientific investigation, and to examine the principles of the protection mechanism for this right, examined in the article. The comparative analysis has allowed us to highlight aspects regarding the compatibility of national legislation on property protection with the standards of the ECHR. The historical method, inherent to research in the field of legal sciences, facilitates the examination of the factors that have influenced the development of legal norms concerning property protection. This method helps identify important material legal sources to understand the evolution of the legal reasoning behind the ECHR’s decisions on property protection cases. As we will observe in this work, the European Court often engages in historical analysis when grounding its decisions, especially in cases of the nationalisation of private property. Dynamic analysis (from a forward-looking perspective) is relevant whenever we need to plan amendments to national legislation in the process of implementing the European Court of Human Rights’ decisions concerning Article 1 of Protocol No. 1 to the European Convention on Human Rights.Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms, expropriation, possessions, protection of property